A rare complication in a patient taking rivaroxaban: Alveolar hemorrhage - Salih Kılıç; Erhan Saraçoğlu; Gülin Alkan (Türk Kardiyoloji Derneği Arşivi, 2018)
Alveolar hemorrhage (AH) is a heterogeneous clinical syndrome with a high mortality rate that is characterized by extensive bleeding into the alveolar spaces. AH usually develops secondary to immunological disease and, less frequently, to drug use. Presently described is the case of an 86-year-old woman with AH who had been using rivaroxaban for 6 months.